The Halal Certification Policy in Indonesia and the World Trade Organization - Alda Meydiyana Sagita; Sasmini (International Journal of Integrated Science and Technology, 2024)
International trade between countries concerns the formation of multilateral relations between various countries to facilitate cooperation in the field of international trade, so international organizations were formed that regulate trade relations between countries so that international trade can be easier, and there are no obstacles in international relations trade between countries, namely the WTO (World Trade Organization). With the formation of the WTO, there are agreements that have been agreed upon by member countries. Indonesia is a member of the WTO and is bound by the provisions established in 1995 which were marked by the ratification of the WTO agreement through Law Number 7 of 1994. Indonesia must comply with all WTO provisions in order to increase market access in other member countries. The Indonesian state has a policy in the form of a halal policy which is regulated in UU/33/2014 concerning Halal Product Guarantees. The existence of a policy stating that all products, both domestic and imported, must be halal certified is considered to be an obstacle to international trade because it is contrary to GATT policy and the TBT Agreement. The method used is normative legal research and the data used is secondary data sourced from primary legal materials and tertiary legal materials. The approach used is a historical, explanatory and legal synchronization approach. Data collection techniques through literature studies and studied using qualitative analysis.